Pyramiding white rust resistance and Alternaria blight tolerance in low erucic Brassica juncea using Brassica carinata - Kadambari Gupta,; Deepak Prem,; Abha Agnihotri, (Journal of Oilseed Brassica, 2026)
The present study was undertaken to incorporate resistance to fungal diseases white rust (WR) andAlternaria blight (AB) in low erucic acid Brassica juncea from B. carinata through interspecifichybridization aided by ovule culture. Hybrids characterized through ISSR markers and morphological traits,indicated intermediate nature with strong influence of pollen donor. The hybrids showed high variation inmorphology (6% B. juncea type plants in F2 to 100% in BC2) and exhibited high tolerance to both WR andAB in subsequent backcross generations under epiphytotic conditions. B. juncea type plants were identifiedfrom BC2 and BC1self progeny with no detectable erucic and high oleic acid (44.7%) content along with hightolerance to both WR and AB.